Infection and death by COVID-19 in a cohort of healthcare workers in Mexico - Eduardo Robles-Pérez; Belinda González-Díaz; Maximino Miranda-García; Victor Hugo Borja-Aburto (Nordic Association of Occupational Safety and Health (NOROSH), 2021)
OBJECTIVE: This study aimed to estimate the risk of SARS-Cov2 infection and severe COVID-19 among healthcare workers from a major social security system. METHODS: This study actively followed a cohort of social security workers from March to December 2020 to determine the number of laboratory-confirmed symptomatic cases, asymptomatic associated contacts and COVID-19-associated hospitalizations and deaths. Workers were classified into those providing direct care to infected patients (COVID teams), other active healthcare workers (OAHCW), and workers under home protection (HPW). The number of cases and rates were also estimated by job category. RESULTS: Among a total of 542 381 workers, 41 461 were granted stay-at-home protection due to advanced age or comorbidities. Among the 500 920 total active workers, 85 477 and 283 884 were classified into COVID teams and OAHCW, respectively. Infection rates for COVID teams, OAHCW, and HPW were 20.1% [95% confidence interval (CI) 19.8-20.4], 13.7% (95% CI 15.0-15.3), and 12.2% (95% CI 11.8-12.5), respectively. The risk of hospitalization was higher among HPW. COVID teams had lower mortality rate per 10 000 workers compared to HPW (5.0, 95% CI 4.0-7.0 versus 18.1, 95% CI 14.0-23.0). Compared to administrative workers, ambulance personnel (RR 1.20; 95% CI 1.09-1.32), social workers (RR 1.16; 95% CI 1.08-1.24), patient transporters (RR 1.15; 95% CI 1.09-1.22) and nurses (RR 1.13; 95% CI 1.10-1.15) had a higher risk of infection after adjusting for age and gender. Crude differences in mortality rates were observed according to job category, which could be explained by differences in age, sex, and comorbidity distribution. Diabetes, obesity, hypertension, hemolytic anemia, and HIV were associated with increased fatality rates. CONCLUSIONS: COVID team workers had higher infection rates compared to the total population of active workers and HPW. Doctors had lower risk of infection than respiratory therapists, nurses, and patient transporters, among whom interventions should be reconsidered to reduce risks. The presence of comorbidities, such as diabetes, obesity, arterial hypertension, hemolytic anemia, and HIV, increased the likelihood of complications caused by COVID-19, culminating in a poor prognosis.